PEMEROLEHAN BAHASA PADA BAYI DAN ANAK - Chairunnisa Chairunnisa (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
This paper explained about the language acquisition of the infant and child. The language acquisition involved the research method and language development. Some researcher conducted the research by using some methods and designs such as diary and parental report, interview, observation, and experiment. The researcher also identified the process of childrens’ language acquisition and also identified the process of acquisition. In this paper also describe the speech perception development, process of language acquisition from phonology, sintaxis, and lexical. Not only explained about the process and kinds of childreens’ language acquisition but also it is explained the way child give the sense of the words or related to pragmatic.Keywords: Language Acquisition